Community electricity and storage central management for multi-dwelling developments: an analysis of operating options - Tomc, Elizabeth; Vassallo, Anthony M (International Journal of Sustainable Energy Planning and Management, 2018)
A combination of PV, storage and energy management in multi-dwelling developments can be very effective in utilising load diversity and reducing grid dependence. Sharing PV and electricity storage resources within a community renewable energy network (CREN) via an energy management system (EMS) shifts the peak individual loads to times that the grid considers off-peak periods - i.e. night time – so managed off-peak charging and a retail plan with the lowest off-peak pricing affords the community savings in the order of 95.5% compared to the traditional individual grid connection. The balancing performed by the EMS eliminates the paradox of concomitant demand and supply from/to grid that occurs when some of the individual systems in the community have available charge while others don’t. The optimisation of off-peak charging avoids 54% of redundant charge which is a financial gain in jurisdictions where feed-in tariffs are much lower than supply charges. Even though this study focuses on an Australian case study it provides a tool that allows the performance of the same analysis for other specific sites and load profiles.